The effect of third party funds, capital adequacy ratio, and financing to deposit ratio on profitability with non-performing financing as moderation variables in Syari’ah People’s Finance Bank Bhakti Sumekar Sumenep - Mujairimi (Technium Social Sciences Journal, 2023)
This study aims to empirically prove the effect of third party funds, capital adequacy ratio and financing to deposit ratio on profitability with non-performing financing as a moderating variable in the Islamic people’s financing bank (BPRS) Bhakti Sumekar Sumenep. The sample in this research is quarterly financial reports and the data used are 40 companies’ quarterly financial reports with data analysis method using multiple linear regression. The results of the study show that DPK, FDR and NPF have no effect on the profitability of the Islamic people’s financing bank (BPRS) Bhakti Sumekar Sumenep. While CAR has an effect on ROA. The results of the analysis on the moderating variable show that NPF is not able to moderate the effect of DPK, CAR and FDR on ROA.